White Marble as an Alternative Surface for Removal of Toxic Dyes (Methylene Blue) from Aqueous Solutions - Ayad F. Alkaim, Aseel M. Ajobree (International Journal of Advanced Science and Technology, 2020)
The preparation of white marble with HCl activation and its capability to remove toxic dye (Methuen blue MB), from aqueous solutions were reported in this study. The adsorbent was characterized with (FT-IR) Fourier transform infrared spectrophotometer, Several physiochemical parameters like , agitation  time, primary concentration dye, adsorbent amount and temperature were studied in a batch-adsorption system. Data appeared of the adsorption of MB dye find to rise with increase in primary concentration dye, and agitation  time but reductions with the temperature and  mass adsorbent of the method. The concentration of dye was measured before and after adsorption through utilizing  UV-Visible spectrophotometer at 663 nm.